2018
DOI: 10.4166/kjg.2018.71.3.153
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Malignancies in Patients with Inconclusive or Negative Results of Endoscopic Ultrasound-guided Fine-needle Aspiration for Solid Pancreatic Masses

Abstract: Background/Aims: This study analyzed the diagnostic accuracy of endoscopic ultrasound-guided fine needle aspiration (EUS-FNA) for pancreatic solid masses in patients with or without chronic pancreatitis as well as the clinical parameters relevant to a malignancy when EUS-FNA was negative or inconclusive. Methods: A total of 97 patients, who underwent EUS-FNA for solid pancreatic masses over 2 years at a single institution, were evaluated. All patients underwent EUS-FNA for 3-5 passes with 22 or 25 G needles wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…[1][2][3][4][5][6] Meanwhile, previous reports for EUS-guided tissue sampling (EUS-TS) using fine-needle aspiration or biopsy provide higher diagnostic yields for solid pancreatic masses, and EUS-TS has been increasingly used to overcome the moderate diagnostic yield of ERCP-TS. [7][8][9] Furthermore, in patients with suspected biliary stricture, the diagnostic yield of EUS-TS is reportedly superior to that of ERCP-TS when tissue samples are obtained from lesions in the pancreas, lymph node (LN), and others that cause biliary obstruction.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6] Meanwhile, previous reports for EUS-guided tissue sampling (EUS-TS) using fine-needle aspiration or biopsy provide higher diagnostic yields for solid pancreatic masses, and EUS-TS has been increasingly used to overcome the moderate diagnostic yield of ERCP-TS. [7][8][9] Furthermore, in patients with suspected biliary stricture, the diagnostic yield of EUS-TS is reportedly superior to that of ERCP-TS when tissue samples are obtained from lesions in the pancreas, lymph node (LN), and others that cause biliary obstruction.…”
Section: Introductionmentioning
confidence: 99%
“…15 Therefore, even if a biopsy successfully samples a PDAC mass, it may not collect enough malignant cells to confidently make a diagnosis, leading to nondiagnostic results. Previous studies of EUS-FNAs on patients with PDAC have found biopsy results to be atypical, suspicious, or inconclusive in 9%-15% [16][17][18][19] and benign or negative in 4%-11%. [12][13][14][19][20][21] The common occurrence of nondiagnostic biopsy results prompts 6%-16% of patients to get a second biopsy and 1%-2% to get a third 22,23 despite delays and lower yields.…”
Section: Introductionmentioning
confidence: 91%